Sound documentary, the alternative to tell the reality from a gender perspective: Análisis de casos en España y Latinoamérica - López Villafranca, Paloma (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
The objective of this article is to carry out a case study of 10 documentaries from Spain and Latin America to show how the reality of women is represented. The methodology of content analysis is used through formal, content and aesthetic variables. These are personal stories of women from low social class, middle age, in rural areas, who denounce injustices related to mistreatment, exploitation or abortion, compared to historical documentaries starring women from high social class who are pioneers in their field. It is concluded that the role of the narrator influences the story, with differences in the production between Spanish and Latin American documentaries.